Epoxidized natural rubber 50 FBG sensor for pressure applications - Siti Fatimah Harun (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
Due to the problems discussed, the research to study the performance of ENR50 coated FBG sensor was done and compared with the bare FBG sensor. Then, the performance of ENR50 coated FBG was analyzed towards a few of pressure applications which os weight and level/depth ; the objectives of this research can be concluded as follows ; to design an ENR50 polymer coated FBG sensor tetsbed ; to compare the performance of ENR50 coated FBG sensor towards the bare FBG sensor through theoretical and experimental work ; to analyze the performance of ENR50 coated FBG for pressure applications which are weight and level or depth.